Morph-physiological cellular changes during cardiac-pulmonary-cerebral resuscitation - Ana María Barcia Armas; Claudia Díaz de la Rosa; Jeisy Rivero Morey; Víctor René Navarro Machado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Cell suffer structural and metabolic changes in stress situations,which allow them to maintain an adequate homeostasis and avoid death . This bibliographic review had the objective of describing the main morph-physiological changes which occur in cardiac failure and cardiac-pulmonary-cerebral resuscitation. The method was documentary reviewing (database Regional SciELO, PubMed, Cochrane and Infomed), developed during the first semester of 2018. Twenty eight references were selected. It was concluded that there are cellular changes during circulatory stop, the procedures of resuscitation and re-perfusion. In cardiac failure, cellular changes are expressed in all the organelles. And may cause death due to necroses. During re-perfusion new structural changes occur, for calcium entrance, sodium disturbances, production of free radicals and swelling. Morph.physiological changes depend on previous metabolic condition, time of cardiac failure and the successful establishment of resuscitation measures.